Enhancing the use of e-learning systems in the public sector: a behavioural intention perspective. (2016) - Hung, Shin-Yuan; Chen, Charlie C.; Yeh, Ralph Keng-Jung; Huang, Li-Chia
Using electronic learning (e-learning) can enhance a civil servant's proficiency in performing quality service to civilians. However, civil servants tend to be passive adopters of innovative technology. Increasing the intention of them to adopt e-learning has the potential of improving the quality of civil services. This study proposes a research model based on the Decomposed Theory of Planned Behaviour. 416 responses were collected from four counties of Taiwan. The analysis results indicate that attitude and behavioural control have a positive effect on a civil servant's behavioural intention of adopting e-learning. However, the subjective norm has a negative effect on behavioural intention. Usefulness, compatibility, and ease of use have a positive effect on attitude. Interpersonal influence and external influence have a positive effect on the subjective norm. Self-efficacy and professional core competency have a positive effect on behavioural control. Academic and practical implications are drawn from these findings.